2011
DOI: 10.1348/2044-8279.002009
|View full text |Cite
|
Sign up to set email alerts
|

Trait emotional intelligence influences on academic achievement and school behaviour

Abstract: BACKGROUND. Trait emotional intelligence (trait EI or trait emotional self-efficacy) refers to individuals' emotion-related self-perceptions (Petrides, Furnham, & Mavroveli, 2007). The children's trait EI sampling domain provides comprehensive coverage of their affective personality. Preliminary evidence shows that the construct has important implications for children's psychological and behavioural adjustment. AIMS. This study investigates the associations between trait EI and school outcomes, such as perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
1
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(182 citation statements)
references
References 101 publications
(135 reference statements)
14
138
1
13
Order By: Relevance
“…Empirical evidence has also shown that trait EI has a positive effect on happiness, life satisfaction, affect (Platsidou, 2013;Chamorro-Premuzic, Furnham & Lewis, 2007;Petrides & Furnham, 2003), and academic success, primarily among at risk students (Mavroveli, Sanchez-Ruiz, 2010;Parker, Summerfeldt, Hogan & Majeski, 2004;. Experimental findings have provided insight regarding the connection between trait EI and academic performance.…”
Section: Trait Emotional Intelligence (Ei) and Educational Outcomesmentioning
confidence: 99%
“…Empirical evidence has also shown that trait EI has a positive effect on happiness, life satisfaction, affect (Platsidou, 2013;Chamorro-Premuzic, Furnham & Lewis, 2007;Petrides & Furnham, 2003), and academic success, primarily among at risk students (Mavroveli, Sanchez-Ruiz, 2010;Parker, Summerfeldt, Hogan & Majeski, 2004;. Experimental findings have provided insight regarding the connection between trait EI and academic performance.…”
Section: Trait Emotional Intelligence (Ei) and Educational Outcomesmentioning
confidence: 99%
“…In Sri Lanka, school adolescents face a lot emotional challenge in an overly competitive academic environment. While emotional coaching by parents being helpful in early years of life, similar coaching by teachers at schools is equally important during adolescence in the later stages of development [8].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Petrides, Sangareau, Furnham, and Frederickson (2006) demonstrated that children with high trait EI scores received more nominations from peers and teachers for positive social attributes, such as cooperation and leadership, and fewer nominations for negative social characteristics, such as aggression and delinquency (for similar results see Mavroveli & Sánchez-Ruiz, 2011;Santesso, Dana, Schmidt, & Segalowitz, 2006). However, the above-mentioned studies concern mainly children.…”
Section: Trait Emotional Intelligencementioning
confidence: 93%